Proposal of an interpretative theoretical frame about sport associationism in Spain - N. Puig; A. Moreno; C. López (Asociación Española de Ciencias del Deporte, 2010)
The article is a theoretical essay about sport organisations in Spain. It has two parts. The first one deals with the heterogeneity of sport organisations. This is analized from an historical and present perspective. The second part deals with the context of sport oganisations. It is considered that sport, organisational, political and social aspects are fundamental to understand the present situation of sport organisations in Spain. In analysing them, problems related with different kind of sport organisations are raised. Conclusions are summarising the main ideas developped. KEY WORDS: Sport associationism